Universal Bacterium-Vectored COVID-19 Vaccine Expressing Early SARS-CoV-2 Conserved Proteins Cross-Protects Against Late Variants in Hamsters - Qingmei Jia; Helle Bielefeldt-Ohmann; Saša Masleša-Galić; Richard A. Bowen; Marcus A. Horwitz (Vaccines, 2025)
Background/Objectives: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of Coronavirus Disease 2019 (COVID-19), has rapidly evolved, giving rise to multiple Variants of Concern—including Alpha, Beta, Gamma, Delta, and Omicron—which emerged independently across different regions. Licensed COVID-19 vaccines primarily target the highly mutable spike protein, resulting in reduced efficacy due to immune escape by emerging variants. Previously, we developed a live attenuated Francisella tularensis LVS ΔcapB single-vector platform COVID-19 vaccine, rLVS ΔcapB/MN, expressing the conserved membrane (M) and nucleocapsid (N) proteins from the early SARS-CoV-2 WA-01/2020 strain. In this study, we evaluate the efficacy of rLVS ΔcapB/MN and an enhanced version, rLVS ΔcapB::RdRp/MN, which additionally expresses the conserved RNA-dependent RNA polymerase (RdRp) protein from the same strain, in a hamster model. Methods: Both vaccine candidates were administered orally or intranasally to golden Syrian hamsters (equal numbers of males and females) and evaluated against intranasal challenge with SARS-CoV-2 Delta (B.1.617.2-AY.1) and Omicron (BA.5) variants. Results: Vaccinated animals developed robust, TH1-biased IgG responses specific to the nucleocapsid protein. Following SARS-CoV-2 challenge, immunized hamsters exhibited reduced weight loss, lower oropharyngeal and lung viral titers, and improved lung pathology scores compared with unvaccinated controls. Conclusion: These findings support the potential of this universal vaccine to provide broad protection against current and future SARS-CoV-2 variants, with minimal need for updating.